THE RELATION OF SLEEP RESPIRATION DISORDERS AND CARDIOVASCULAR RISK - E. A. Dubinina; L. S. Korostovtseva; О. P. Rotar; S. О. Kravchenko; М. A. Boyarinova; A. V. Orlov; V. N. Solntsev; Yu. V. Sviryaev; А. N. Alyokhin; A. О. Konradi (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To assess the relation of obstructive sleep apnea syndrome (OSAS) by the data of Berlin questionnaire and risk of fatal cardiovascular events. Material and methods. Totally, 275 persons  studied (115 males, 160 females)  age  25-64 y.o., with unknown cardiovascular  complications, underwent structured  interview. The risk of sleep-disordered breathing was assessed by Berlin questionnaire, cardiovascular risk — by SCORE. Anthropometric  parameters  were  studied,   as  lipid profile,  fasting glucose, uric acid, creatinine, C-reactive protein, adiponectin, leptin. Results. The increased  OSAS risk according to Berlin questionnaire was found in 7,3% of the studies. Most (90,0%) common was concomitance of the  components   of OSAS such  as  snoring/stops of respiration  and cardiometabolic disorders. Males more frequently complained on snoring/ stops of breathing — 21,7% vs 6,3% (p=0,001), that determined  higher general risk of OSAS among them comparing to women — 11,3% vs 4,4% (p=0,03).  For males  (1,7%)  and  females  (3,1%)  the  complaints  on daytime sleepiness were less common. Among those 40 y.o. and older the increased  risk of OSAS was found in 9,8%, comparing to 1,2% younger than  40  y.o.  (p=0,01).  In higher  OSAS risk there  was  higher  total cholesterol  — 6,10±0,18  vs 5,53±0,09  mM/L (p=0,05) and low density lipoproteides — 4,17±0,19 vs 3,59±0,08 mM/L (p=0,02); they were more often overweight — body mass  index 31,73±1,19  vs 27,71±0,38  kg/m2 (p=0,001),   and   had   higher  systolic  pressure  —  134,89±4,96   vs 126,72±1,18  mmHg. (p=0,04) and diastolic pressure — 84,26±2,69  vs 78,55±0,80  mmHg (p=0,03).  Respondents with higher  risk of OSAS regardless the  gender,  did not differ by SCORE. While determine  the specific combinations of OSAS components, there was no independent significance of snoring/respiration  pauses  and daytime sleepiness  in the total cardiovascular risk by SCORE.Conclusion. In the Russian population, higher OSAS risk is associated with the signs of metabolic syndrome. Berlin questionnaire does not reveal the subgroups of those who have OSAS risk together with cardiovascular risk.